Trends in fertility intentions and contraceptive practices in the context of COVID-19 in sub-Saharan Africa: insights from four national and regional population-based cohorts. Issue 1 (18th January 2023) - Moreau, Caroline; Karp, Celia; Wood, Shannon; Williams, Kelsey; Olaolorun, Funmilola M; Akilimali, Pierre; Guiella, Georges; Gichangi, Peter; Zimmerman, Linnea; Anglewicz, Philip
Abstract : Objectives: Studies in several sub-Saharan geographies conducted early in the COVID-19 pandemic suggested little impact on contraceptive behaviours. Initial results may mask widening disparities with rising poverty, and changes to women's pregnancy desires and contraceptive use amid prolonged health service disruptions. This study examined trends in contraceptive behaviours in four sub-Saharan African settings 1 year into the pandemic. Design: Nationally and regionally representative longitudinal surveys. Setting: Burkina Faso, Kenya, Democratic Republic of Congo (Kinshasa) and Nigeria (Lagos). Participants: Women aged 15–49 years with sample size ranging from 1469 in Nigeria to 9477 in Kenya. Outcome measures: Fertility preferences, contraceptive use and unintended pregnancies measured before COVID-19 (November 2019 to January 2020) and during COVID-19 (November 2020 to January 2021). Analysis: We described population-level and individual-level changes by socioeconomic characteristics using generalised equation modelling. We used logistic regression models to identify factors related to contraceptive adoption and discontinuation and to experiencing an unintended pregnancy. Results: At the population level, we found no change in women's exposure to unintended pregnancy risk, alongside 5–9 percentage point increases in contraceptive prevalence in Burkina Faso, Kenya and Lagos. Reliance on provider-dependent methods dropped by 2 and 4 percentage points in Kenya and Burkina Faso, respectively, although these declines were not statistically significant. Between 1.0% and 2.8% of women across sites experienced an unintended pregnancy during COVID-19, with no significant change over time. Individual-level trajectories showed contraceptive adoption was more common than discontinuation in Burkina Faso, Kenya and Lagos, with little difference by sociodemographic characteristics. Women's COVID-19-related economic vulnerability was unrelated to unintended pregnancy across sites. Conclusions: This study highlights the resilience of African women across diverse settings in sustaining contraceptive practices amid the COVID-19 pandemic. However, with reports of rising poverty in sub-Saharan Africa, there is continued need to monitor access to essential sexual and reproductive health services.